1999
DOI: 10.1017/s135583829998130x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of splice sites to antisense oligonucleotides in vivo

Abstract: A series of HeLa cell lines which stably express b-globin pre-mRNAs carrying point mutations at nt 654, 705, or 745 of intron 2 has been developed. The mutations generate aberrant 59 splice sites and activate a common 39 cryptic splice site upstream leading to aberrantly spliced b-globin mRNA. Antisense oligonucleotides, which in vivo blocked aberrant splice sites and restored correct splicing of the pre-mRNA, revealed major differences in the sensitivity of these sites to antisense probes. Although the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
6
34
0
Order By: Relevance
“…was ϳ8 times lower than that of the 5Ј splice site (26). The difference in the accessibilities of the 3Ј and 5Ј aberrant splice sites in IVS2-705 pre-mRNA to modified U7 snRNPs, particles much larger than the oligonucleotides (Ref.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…was ϳ8 times lower than that of the 5Ј splice site (26). The difference in the accessibilities of the 3Ј and 5Ј aberrant splice sites in IVS2-705 pre-mRNA to modified U7 snRNPs, particles much larger than the oligonucleotides (Ref.…”
Section: Discussionmentioning
confidence: 95%
“…Restoration of gene activity was accomplished by targeting the splice sites created or activated by several mutations in thalassemia (23)(24)(25)(26), cystic fibrosis (27), and in a mouse mdx model of Duchenne muscular dystrophy (28). Thus, modification of splicing by treatment with antisense oligonucleotides provides a potential alternative to gene therapy protocols involving the replacement of defective genes.…”
mentioning
confidence: 99%
“…Work in this laboratory showed that splice-switching oligonucleotides (SSOs), which block aberrant splice sites in IVS2-654 and other pre-mRNAs (IVS1-5, IVS1-6, IVS1-110, IVS2-705, and IVS2-745) as well as in the coding sequence (HbE) of the ␤-globin gene, force the splicing machinery to reselect the existing correct splice sites, repairing the splicing pattern of ␤-globin pre-mRNA. This repair, which restores production of correctly spliced ␤-globin mRNA and protein, was accomplished in several in vitro systems and ex vivo in erythroid progenitor cells from thalassemic patients (6)(7)(8)(9)(10)(11)(12). In this study, we investigated the effectiveness in thalassemic splicing correction of a modified morpholino oligomer, SSO 654-P005, in a mouse model of IVS2-654 ␤-thalassemia.…”
mentioning
confidence: 99%
“…16,30 HeLa cell lines EGFP-654 and EGFP-705U expressed a construct in which the coding region of enhanced green fluorescent protein (EGFP) was interrupted by the mutated ␤-globin intron. 31 All cell lines were grown at 37°C, 5% CO 2 in minimal essential medium modified for suspension cells (S-MEM) supplemented with 5% fetal calf sera, 5% horse sera, 50 g/mL gentamicin, and 200 g/mL kanamycin.…”
Section: Cell Linesmentioning
confidence: 99%
“…Nevertheless, in these cells the level of correction by all 3 constructs was lower than that seen in the transfected EGFP-705U cell line ( Table 1), indicating that EGFP-654 pre-mRNA might be less susceptible to modification of splicing by antisense sequences than its 705U counterpart (see below and "Discussion"). 30 ␤-Globin IVS2-654, IVS2-705, and IVS2-745 pre-mRNAs as targets…”
Section: Modification Of Egfp-654 and Egfp-705u Splicing By U7623 Snrnamentioning
confidence: 99%